Interface treatment material with self-curing and gradient moisture absorption function and preparation method thereof
Patent Information
- Application Number
- CN202611228493.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-09-15
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application relates to the field of building materials technology, and in particular to an interface treatment material with self-curing and gradient moisture absorption functions and its preparation method. Background Technology
[0002] In building decoration and renovation projects, substrate treatment is a crucial step affecting the adhesion quality of the finishing layer and the durability of the project. Whether it's tiling in kitchens and bathrooms, waterproofing the basement, or constructing the finishing layer on exterior walls, the interface layer between the substrate and the finishing material bears multiple functions, including stress transfer, deformation coordination, and environmental barrier. However, existing interface treatment materials generally suffer from problems such as limited functionality, poor adaptability to damp substrates, and susceptibility to cracking when applied in thin layers, making it difficult to meet the increasingly complex engineering requirements.
[0003] In summary, existing interface treatment materials share the following common technical shortcomings: I. Low functional integration. Existing products mostly focus on a single function, such as bonding enhancement, waterproofing, or moisture absorption. They lack material designs that integrate multiple functions such as "moisture absorption and regulation, interface enhancement, and crack control" into one unit. This often leads to the need for multiple processes and materials in actual engineering projects, which increases construction complexity and overall cost.
[0004] Second, it is difficult to synergistically improve hygroscopic properties and mechanical properties. While the addition of hygroscopic components such as diatomaceous earth can enhance moisture regulation, their porous structure reduces the material's density and strength, leading to decreased adhesion. Maintaining or even improving interfacial bonding strength while ensuring high hygroscopicity remains a technical challenge that current technologies have not yet effectively addressed.
[0005] Third, thin-layer application is prone to cracking and lacks an effective shrinkage compensation mechanism. Interface treatment materials are usually applied in thin layers (2-3 mm), resulting in rapid early water loss and concentrated shrinkage stress, making them highly susceptible to drying shrinkage cracks. Existing products mostly rely on single expanding agents or fibers for improvement, but lack a systematic matching design for the hydration-expansion-shrinkage timeline, resulting in limited crack resistance.
[0006] Fourth, poor adaptability to damp substrates. Existing interface materials have strict requirements on the moisture content of the substrate, usually requiring the substrate to be dry or have a moisture content below 8%, otherwise it is difficult to guarantee the bonding quality. However, in actual engineering projects, scenarios such as basements, rainy season construction, and newly poured concrete often face the problem of damp substrates. The low construction tolerance of existing materials has become a weak link in project quality control.
[0007] 5. Lack of active humidity control capability during service life. Existing materials lose their ability to influence the interface microenvironment after hardening, making it impossible to continuously regulate humidity during building use. In high-humidity environments such as basements and kitchens / bathrooms, the interface layer is subjected to long-term water vapor infiltration pressure, easily leading to durability problems such as blistering, peeling, and mold growth in the finish layer.
[0008] Therefore, developing an interface treatment material that integrates self-maintenance, gradient moisture absorption, and multiple crack resistance functions has become an urgent technical challenge to be solved in this field. Summary of the Invention
[0009] To simultaneously address the technical challenges of balancing hygroscopic and mechanical properties, poor adaptability to damp substrates, and easy cracking during thin-layer construction in existing technologies, this application provides an interface treatment material with self-curing and gradient hygroscopic functions, comprising the following raw materials in parts by weight: Cementitious components: 30-50 parts of ordinary 425 silicate cement, 5-15 parts of sulfoaluminate cement, and 2-8 parts of α-hemihydrate gypsum; Porous mineral composition: diatomite 3-5 parts, zeolite 3-5 parts, attapulgite 2-4 parts, sepiolite 1-3 parts; Filler composition: 5-12 parts fly ash, 2-8 parts silica fume, and 10-20 parts heavy calcium carbonate; Additives: 0.3-0.8 parts cellulose ether, 1-3 parts swelling agent, 0.1-0.5 parts water-reducing agent; Reinforcing component: 2-8 parts.
[0010] This invention first constructs a ternary cementitious system consisting of "ordinary Portland cement + sulfur-aluminate cement + α-hemihydrate gypsum". Existing products are mostly single-component ordinary Portland cement or ordinary Portland cement + polymer, lacking active control over the hydration process. This invention, based on a ternary system, achieves adjustable setting time (30–120 min), controllable early expansion (0.02%–0.08%), and a 28-day shrinkage rate ≤2.0 × 10⁻⁶. -4 Secondly, a multi-level pore structure is constructed by blending four porous minerals—diatomite, zeolite, attapulgite, and sepiolite—in a specific ratio, simultaneously achieving the dual functions of self-curing during construction and humidity regulation during service. Based on a crack-resistant design that matches the "hydration-expansion-shrinkage" timeline, the proportions of the ternary cementitious system, the dosage of the expanding agent, and the water absorption and release characteristics of the porous mineral components are adjusted to achieve a match between hydration heat release, volume expansion, and drying shrinkage on the time axis, maximizing the offsetting of shrinkage stress.
[0011] In some embodiments, the reinforcing component includes: 2-5 parts of redispersible latex powder, 0.2-0.6 parts of polypropylene fiber, and 0.5-2 parts of whiskers.
[0012] Most commercially available products only add fibers or polymer powder, lacking a multi-scale synergistic reinforcement design. This invention introduces whiskers in synergy with polypropylene fibers and redispersible latex powder to construct a three-level reinforcement network of "nano-micro-millimeter". Whiskers fill microcracks, forming a "bridging effect" in micro-regions to prevent microcrack propagation; the three-dimensional network distribution of fibers bears macro-stress and improves toughness; polymer powder encapsulates whiskers and fibers, enhancing interfacial adhesion and forming an overall reinforcement system.
[0013] In some embodiments, the preparation method of the reinforcing component includes: copolymerizing vinyl silane-modified whiskers and vinyl silane-modified polypropylene fibers with acrylic monomers and styrene to obtain a whisker-fiber component, which is then mixed with redispersible latex powder.
[0014] Preferably, the vinylsilane-modified whiskers are obtained by modification with 5-hexenyltrimethoxysilane.
[0015] Preferably, the whiskers are selected from one or both of calcium sulfate whiskers and calcium carbonate whiskers.
[0016] Preferably, the whiskers have an aspect ratio of 50 to 100 and a diameter of 1 to 4 μm.
[0017] Preferably, the polypropylene fiber has a diameter of 18–48 μm and a length of 6–12 mm.
[0018] Preferably, the redispersible latex powder is VAE redispersible latex powder.
[0019] The inventors further improved the preparation process of the reinforcing components. Compared with simple physical blending into the material, the above preparation method achieved significantly improved adhesion and compressive strength. This application obtains whisker-grafted polypropylene fibers by copolymerizing vinyl silane-modified whiskers, vinyl silane-modified polypropylene fibers, acrylic monomers, and styrene. The grafted segments include acrylic-styrene copolymer segments. The polypropylene fibers construct a macroscopic three-dimensional skeleton and bear macroscopic stress. The whiskers grafted onto the fibers act like microscopic tentacles, not only bridging microcracks themselves but also efficiently transferring micro-stress to the fiber skeleton through chemical bonding with the fibers, achieving a better reinforcement effect. When microcracks propagate, the moderate debonding and pull-out process of the whiskers at the matrix interface consumes a large amount of energy. At the same time, the grafted whiskers, acting as a bridge, transfer stress to the fibers, avoiding excessive stress concentration at a certain point, thereby achieving reinforcement and toughening. The preparation method designed in this application not only achieves the grafting of whiskers and polypropylene fibers, but also introduces styrene-acrylic segments. These segments possess the high water resistance and high strength of styrene-acrylic rubber powder, and have strong adhesion to conventional VAE redispersible latex powder used in construction. On the one hand, this allows the redispersible latex powder to better encapsulate and enhance the interfacial bonding between the whiskers and fibers. On the other hand, while the redispersible latex itself possesses high strength and high water resistance, its flexibility is generally low, whereas VAE redispersible latex powder has good flexibility but moderate water resistance. Therefore, the two form a good synergistic effect. After compounding, the material has sufficient strength to resist external forces and good toughness, making it less prone to cracking. Therefore, when vinyl silane-modified whiskers, vinyl silane-modified polypropylene fibers, acrylate, and styrene are copolymerized to obtain a whisker-fiber component, and then mixed with redispersible latex powder in the system, a three-dimensional network structure that combines rigidity and flexibility, strong water resistance, and continuous stress release is achieved, thereby significantly improving compressive strength, crack resistance, and adhesion. 5-Hexenyltrimethoxysilane modified whiskers, based on the long hexene chain, give the whiskers a higher degree of freedom, which is more conducive to achieving micro-gap filling than KH570, thereby improving crack resistance.
[0020] In some embodiments, the expanding agent is selected from one or more of calcium sulfoaluminate expanding agents, calcium oxide expanding agents, or calcium sulfoaluminate-calcium oxide composite expanding agents.
[0021] Secondly, this application provides a method for preparing the interface treatment material with self-healing and gradient moisture absorption functions as described in the first aspect of claim, comprising the following steps: Weigh each component according to the formula, put the gelling component, porous mineral component and filler component into the mixer and premix for 5-10 minutes; add the reinforcing component and additives, and continue mixing for 10-15 minutes until uniform; discharge and package.
[0022] The interface treatment material of this application is formulated into an interface solidification and moisture conditioning slurry during application. The solid content of the interface solidification and moisture conditioning slurry is preferably 45%-50%, and the specific content can be adjusted according to the construction site.
[0023] The interface treatment material described in this application is applicable to building surface treatment, including basements, kitchens and bathrooms, exterior walls, underfloor heating protective layers, smooth concrete surfaces, and old tile renovation.
[0024] The materials in this application are suitable for direct application to damp substrates with a moisture content of ≤15%.
[0025] In summary, this application has at least the following beneficial technical effects: 1. This application achieves time-history matching of hydration rate regulation and expansion compensation in the cementitious components, and the porous mineral components achieve a multi-level pore structure. It absorbs excess moisture from the substrate in the early stage of construction and slowly releases it during the hydration exothermic stage, thus achieving self-curing of the cementitious material. The reinforcing components synergistically form a three-level reinforcing network of nano-micro-millimeter and combine with other components to form an interface treatment material. Through the design of the ternary cementitious system, the construction of multi-level pores of the porous mineral composite, the integration of the whisker-fiber-polymer three-dimensional reinforcing network, and the system optimization of hydration-expansion-shrinkage time-history matching, it achieves multi-functional synergy of self-curing during construction, gradient moisture absorption during service, and crack resistance throughout the entire cycle. It fundamentally solves the problems in the existing technology, such as the difficulty in balancing moisture absorption and mechanical properties, easy cracking in thin-layer construction, and poor adaptability to damp substrates.
[0026] 2. This application optimizes the preparation process of the reinforcing component by copolymerizing vinyl silane-modified whiskers, vinyl silane-modified polypropylene fibers, acrylic monomers, and styrene to obtain a whisker-fiber component, which is then mixed with redispersible latex powder in the system to achieve a three-dimensional network structure that combines rigidity and flexibility, has strong water resistance, and continuously releases stress, thereby significantly improving the compressive strength, crack resistance, and adhesion.
[0027] 3. The adaptive construction technology for damp substrates in this application can significantly lower the construction threshold, and is especially suitable for scenarios such as basement construction and construction during the rainy season. Traditional interface agents require a substrate moisture content of ≤8%, otherwise they are prone to blistering; this invention increases the construction tolerance to a substrate moisture content of ≤15%. Through the rapid moisture absorption function of the porous mineral composite and the fast hardening characteristics of the ternary cementitious system, the material can be directly applied under the condition of a substrate moisture content of ≤15%, without the need for pre-drying treatment. Detailed Implementation
[0028] The present application will be further described in detail below through examples.
[0029] The fly ash is grade II fly ash with a density of 800 kg / m³, SiO₂≥45%, and Al₂O₃+Fe₂O₃≤25%; the silica fume particle size is 4μm; the heavy calcium carbonate particle size is 800 mesh; the diatomaceous earth is 200 mesh, the zeolite is 200 mesh, the attapulgite is 200 mesh, and the sepiolite is 200 mesh; the cellulose ether is hydroxypropyl methylcellulose with a viscosity of 100,000; the expanding agent is calcium sulfoaluminate expanding agent; the water reducing agent is polycarboxylate water reducing agent; the redispersible latex powder is VAE redispersible latex powder; the polypropylene fiber diameter is 30μm and the length is 10mm; the whiskers are calcium sulfate whiskers with an aspect ratio of 50 and a diameter of 2μm; other components are all conventional grades in the field or obtained through conventional processes. Example 1
[0030] The interface treatment material has the following components in parts by weight: 38 parts ordinary 425 silicate cement, 10 parts sulfoaluminate cement, 4 parts α-hemihydrate gypsum, 4 parts diatomaceous earth, 4 parts zeolite, 3 parts attapulgite, 2 parts sepiolite, 8 parts fly ash, 5 parts silica fume, 4 parts redispersible latex powder, 0.5 parts cellulose ether, 2 parts expansion agent, 0.4 parts polypropylene fiber, 1 part calcium sulfate whiskers, 0.2 parts water-reducing agent, and 13.9 parts heavy calcium carbonate powder.
[0031] Weigh each component according to the proportion, and put ordinary 425 silicate cement, sulfoaluminate cement, α-hemihydrate gypsum, diatomaceous earth, zeolite, attapulgite, sepiolite, fly ash, silica fume, and heavy calcium carbonate into a mixer for premixing for 8 minutes; add reinforcing components, redispersible latex powder, polypropylene fiber and whiskers, as well as cellulose ether, expanding agent, and water-reducing agent, and continue mixing for 12 minutes until uniform; discharge and package. Example 2
[0032] The difference between Example 2 and Example 1 lies in the formulation. The mass parts of each component are as follows: 32 parts of ordinary 425 silicate cement, 8 parts of sulfoaluminate cement, 3 parts of α-hemihydrate gypsum, 5 parts of diatomaceous earth, 5 parts of zeolite, 4 parts of attapulgite, 3 parts of sepiolite, 7 parts of fly ash, 4 parts of silica fume, 3.5 parts of redispersible latex powder, 0.6 parts of cellulose ether, 1.5 parts of expanding agent, 0.3 parts of polypropylene fiber, 0.8 parts of calcium sulfate whiskers, 0.2 parts of water-reducing agent, and 18.1 parts of heavy calcium carbonate. Example 3
[0033] The difference between Example 3 and Example 1 lies in the formulation. The mass parts of each component are as follows: 42 parts of ordinary 425 silicate cement, 12 parts of sulfoaluminate cement, 5 parts of α-hemihydrate gypsum, 3 parts of diatomaceous earth, 3 parts of zeolite, 2 parts of attapulgite, 1 part of sepiolite, 6 parts of fly ash, 6 parts of silica fume, 4.5 parts of redispersible latex powder, 0.4 parts of cellulose ether, 2.5 parts of expanding agent, 0.5 parts of polypropylene fiber, 1.5 parts of calcium sulfate whiskers, 0.3 parts of water-reducing agent, and 12.8 parts of heavy calcium carbonate. Example 4
[0034] The interface treatment material has the following component mass percentages: 38 parts ordinary 425 silicate cement, 10 parts sulfoaluminate cement, 4 parts α-hemihydrate gypsum, 4 parts diatomaceous earth, 4 parts zeolite, 3 parts attapulgite, 2 parts sepiolite, 8 parts fly ash, 5 parts silica fume, 0.5 parts cellulose ether, 2 parts expanding agent, 0.2 parts water-reducing agent, 13.9 parts heavy calcium carbonate powder, and 5.4 parts reinforcing component. The reinforcing component is prepared as follows: 50 parts of an ethanol-water solution (volume ratio 3:1) are adjusted to pH 4.5, then 0.1 parts of 5-hexenyltrimethoxysilane are added and sonicated for 30 min. Then, 1 part of calcium sulfate whiskers are added, and the mixture is reacted at 450 rpm and 70℃ for 4 h. The mixture is filtered, washed with ethanol, and dried to obtain vinylsilane-modified whiskers. Alternatively, 50 parts of an ethanol-water solution (volume ratio 3:1) are adjusted to pH 4.5, then KH570 is added... 0.04 parts of the hydrolysate were ultrasonicated for 30 min to obtain a hydrolysate. 0.4 parts of polypropylene fiber were plasma-treated (100W, 200s, argon) and then added to the hydrolysate. The reaction was carried out at 450 rpm and 75℃ for 3 h. The mixture was filtered, washed with ethanol, and dried to obtain vinylsilane-modified polypropylene fiber. The modified whiskers, modified polypropylene fiber, 1 part of styrene, 1 part of butyl acrylate, and 1 part of acrylic acid were added to 50 parts of xylene. Azobisisobutyronitrile solution (0.05 parts dissolved in 5 parts of xylene) was added dropwise and the mixture was reacted at 80℃ and 250 rpm for 7 h. The mixture was filtered, washed with ethanol, and dried under vacuum to obtain the product. The product was mixed with 1 part of redispersible latex powder to obtain the reinforcing component.
[0035] Weigh each component according to the proportion, and put ordinary 425 silicate cement, sulfoaluminate cement, α-hemihydrate gypsum, diatomaceous earth, zeolite, attapulgite, sepiolite, fly ash, silica fume, and heavy calcium carbonate into a mixer for premixing for 8 minutes; add reinforcing components, cellulose ether, expanding agent, and water-reducing agent, and continue mixing for 12 minutes until uniform; discharge and package.
[0036] Comparative Example 1 The difference between Comparative Example 1 and Example 1 lies in the formulation. The mass parts of each component are as follows: 52 parts of ordinary 425 silicate cement, 4 parts of diatomaceous earth, 4 parts of zeolite, 3 parts of attapulgite, 2 parts of sepiolite, 8 parts of fly ash, 5 parts of silica fume, 4 parts of redispersible latex powder, 0.5 parts of cellulose ether, 2 parts of expanding agent, 0.4 parts of polypropylene fiber, 1 part of calcium sulfate whiskers, 0.2 parts of water-reducing agent, and 13.9 parts of heavy calcium carbonate.
[0037] Comparative Example 2 The difference between Comparative Example 2 and Example 1 lies in the formulation. The mass parts of each component are as follows: 13 parts diatomaceous earth, 38 parts ordinary 425 silicate cement, 10 parts sulfoaluminate cement, 4 parts α-hemihydrate gypsum, 8 parts fly ash, 5 parts silica fume, 4 parts redispersible latex powder, 0.5 parts cellulose ether, 2 parts expansion agent, 0.4 parts polypropylene fiber, 1 part calcium sulfate whiskers, 0.2 parts water-reducing agent, and 13.9 parts heavy calcium carbonate.
[0038] Comparative Example 3 The difference between Comparative Example 3 and Example 1 lies in the formulation. The mass parts of each component are as follows: 0.2 parts polypropylene fiber, 2 parts redispersible latex powder, 38 parts ordinary 425 silicate cement, 10 parts sulfoaluminate cement, 4 parts α-hemihydrate gypsum, 4 parts diatomaceous earth, 4 parts zeolite, 3 parts attapulgite, 2 parts sepiolite, 8 parts fly ash, 5 parts silica fume, 0.5 parts cellulose ether, 2 parts expanding agent, 0.2 parts water-reducing agent, and 17.1 parts heavy calcium carbonate.
[0039] Comparative Example 4 The difference between Comparative Example 4 and Example 1 lies in the formulation. The mass parts of each component are as follows: 43 parts of ordinary 425 silicate cement, 5 parts of sulfoaluminate cement, 4 parts of α-hemihydrate gypsum, 4 parts of diatomaceous earth, 4 parts of zeolite, 3 parts of attapulgite, 2 parts of sepiolite, 8 parts of fly ash, 5 parts of silica fume, 4 parts of redispersible latex powder, 0.5 parts of cellulose ether, 0.4 parts of polypropylene fiber, 1 part of calcium sulfate whiskers, 0.2 parts of water-reducing agent, and 15.9 parts of heavy calcium carbonate.
[0040] Comparative Example 1 All components are exactly the same as in Example 1. The difference lies in the substrate treatment method during construction: in this comparative example, the substrate is pre-dried to a moisture content of ≤8% before construction, while in Example 1, the substrate moisture content is ≤15% and construction is carried out directly.
[0041] Compared with Example 1, Comparative Example 1 used a single ordinary silicate cement as the cementing system, without introducing sulfoaluminate cement and α-hemihydrate gypsum, in order to compare the effects of the ternary cementing system on early strength development and shrinkage control.
[0042] Compared with Example 1, Comparative Example 2 used a single diatomaceous earth as the hygroscopic component, without introducing zeolite, attapulgite, or sepiolite to construct a multi-level porous structure, in order to compare the effects of porous mineral composites on hygroscopic performance, self-maintenance function, and mechanical properties.
[0043] Compared with Example 1, Comparative Example 3 did not construct a whisker-fiber-polymer three-dimensional reinforcement network to compare the effects of this reinforcement system on crack resistance, fracture energy and bond strength.
[0044] Compared with Example 1, Comparative Example 4 did not use an expansive agent and reduced the amount of sulfoaluminate cement, which weakened the double expansion crack resistance design, in order to compare the effect of the double expansion of expansive agent + sulfoaluminate cement on shrinkage performance and crack resistance.
[0045] Comparative Example 5 differs from Example 1 in that the substrate treatment method during construction is different. This is used to verify the contribution of the self-curing function of porous minerals to the adaptability of construction on damp substrates.
[0046] Performance testing: The examples and comparative examples used materials to prepare interface bonding and moisture-conditioning slurry with a solid content of 50%. Performance testing items included bond strength, 24-hour moisture absorption rate, 28-day shrinkage rate, compressive strength, upper limit of substrate moisture content during construction, and initial drying crack resistance. Bond strength and adhesion strength (immersion in water) were tested according to the methods in JG / T24-2000. Moisture absorption rate, shrinkage rate, and compressive strength were all tested according to JGJ / T 70-2009 "Standard for Basic Performance Test Methods of Building Mortar". The substrate moisture content was tested using the mortar surface moisture meter method specified in JGJ / T299-2013 "Technical Specification for On-site Testing of Building Waterproofing Engineering".
[0047] Table 1 Performance Test Table
[0048] Based on the performance data comparison in Table 1, the analysis shows that: Comparing Comparative Example 1 with Example 1, it can be seen that after replacing the ternary cementitious system with a single ordinary Portland cement, the 1-day compressive strength decreased from 8.5 MPa to 5.8 MPa, a decrease of 31.8%; the 28-day shrinkage rate decreased from 2.1 × 10⁻⁻⁻⁶. 4 Increased to 3.5 × 10⁻ 4 The bond strength decreased from 0.58 MPa to 0.42 MPa, and microcracks appeared in the initial drying crack resistance test. This fully verifies the technical effect of sulfoaluminate cement providing early strength, α-hemihydrate gypsum regulating the hydration rate, and the synergistic compensation of shrinkage in the ternary cementitious system.
[0049] Comparing Comparative Example 2 with Example 1, it can be seen that after replacing the porous mineral composite with a single diatomaceous earth, the 24-hour moisture absorption rate decreased from 15.6% to 10.5%, the bond strength decreased from 0.58 MPa to 0.48 MPa, and the upper limit of the substrate construction moisture content decreased from 15% to 10%. The results demonstrate that the porous mineral composite achieves gradient moisture absorption through a multi-level pore structure, while avoiding the strength reduction caused by excessive moisture-absorbing components.
[0050] Comparing Comparative Example 3 with Example 1, it can be seen that the shrinkage rate after 28 days decreased from 2.1 × 10⁻ ... 4 Increased to 2.8 × 10⁻ 4 The bond strength decreased from 0.58 MPa to 0.46 MPa, and microcracks appeared in the initial drying crack resistance. This is due to the three-dimensional synergistic reinforcement effect of whiskers filling microcracks, fibers bearing macroscopic stress, and polymer film forming a continuous reinforcing phase. Furthermore, Example 4 shows that it is significantly superior to Example 1 in terms of both adhesion and compressive strength, proving that the treatment of the reinforcing component further optimized the performance.
[0051] Comparing Comparative Example 4 with Example 1, it can be seen that after removing the expansive agent and reducing the amount of sulfoaluminate cement, the 28-day shrinkage rate decreased from 2.1 × 10⁻⁻⁻⁶. 4 Increased to 3.2 × 10⁻ 4 Microcracks appeared during the initial drying crack resistance. This demonstrates the technical effect of the dual expansion compensation mechanism of the expansive agent and sulfoaluminate cement in matching the hydration-shrinkage process in time.
[0052] Comparing Comparative Example 1 with Example 1 shows that Example 1 allows direct construction on a substrate with a moisture content ≤15%, and the bonding strength, crack resistance, and other properties do not decrease after construction. Due to the self-curing function of the porous mineral composite, which rapidly absorbs excess moisture from the substrate in the early stages of construction and slowly releases it during the hydration exothermic phase, the adaptability to construction on damp substrates is significantly improved.
[0053] In summary, the present invention achieves a synergistic improvement in moisture absorption, mechanical properties, crack resistance, and construction adaptability by matching the performance of the ternary cementitious system, porous mineral composite, three-dimensional reinforcement network, crack-resistant design, and self-curing function. All innovations have been effectively verified through comparative experiments.
[0054] This invention is not limited to the specific details of the above embodiments. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of this invention, and all such modifications fall within the protection scope of this invention. Furthermore, it should be noted that the various specific technical features described in the above embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, this invention will not describe the various possible combinations separately. Moreover, different embodiments of this invention can also be arbitrarily combined, as long as they do not violate the spirit of this invention, and should also be considered as part of the disclosure of this invention.
Claims
1. An interface treatment material with self-healing and gradient moisture absorption functions, characterized in that, Including the following parts by weight of raw materials: Cementitious components: 30-50 parts of ordinary 425 silicate cement, 5-15 parts of sulfoaluminate cement, and 2-8 parts of α-hemihydrate gypsum; Porous mineral composition: diatomite 3-5 parts, zeolite 3-5 parts, attapulgite 2-4 parts, sepiolite 1-3 parts; Filler composition: 5-12 parts fly ash, 2-8 parts silica fume, and 10-20 parts heavy calcium carbonate; Additives: 0.3-0.8 parts cellulose ether, 1-3 parts swelling agent, 0.1-0.5 parts water-reducing agent; Reinforcing component: 2-8 parts.
2. The interface treatment material with self-healing and gradient moisture absorption functions according to claim 1, characterized in that, The reinforcing components include: 2-5 parts of redispersible latex powder, 0.2-0.6 parts of polypropylene fiber, and 0.5-2 parts of whiskers.
3. The interface treatment material with self-healing and gradient moisture absorption functions according to claim 2, characterized in that, The preparation method of the reinforcing component includes: vinyl silane modified whiskers and vinyl silane modified polypropylene fibers, which are then copolymerized with acrylic monomers and styrene to obtain a whisker-fiber component, and then mixed with redispersible latex powder.
4. The interface treatment material with self-healing and gradient moisture absorption functions according to claim 3, characterized in that, The vinylsilane-modified whiskers were obtained by modification with 5-hexenyltrimethoxysilane.
5. The interface treatment material with self-healing and gradient moisture absorption functions according to claim 2, characterized in that, The whiskers are selected from one or both of calcium sulfate whiskers and calcium carbonate whiskers.
6. The interface treatment material with self-healing and gradient moisture absorption functions according to claim 2, characterized in that, The whiskers have an aspect ratio of 50 to 100 and a diameter of 1 to 4 μm.
7. The interface treatment material with self-healing and gradient moisture absorption functions according to claim 2, characterized in that, The polypropylene fibers have a diameter of 18–48 μm and a length of 6–12 mm.
8. The interface treatment material with self-healing and gradient moisture absorption functions according to claim 1, characterized in that, The expanding agent is selected from one or more of the following: calcium sulfoaluminate expanding agents, calcium oxide expanding agents, or calcium sulfoaluminate-calcium oxide composite expanding agents.
9. A method for preparing an interface-treated material with self-healing and gradient moisture absorption functions as described in any one of claims 1-8, characterized in that, Includes the following steps: Weigh each component according to the formula, put the gelling component, porous mineral component and filler component into the mixer and premix for 5-10 minutes; add the reinforcing component and additives, and continue mixing for 10-15 minutes until uniform; discharge and package.